2014
DOI: 10.1371/journal.pone.0086123
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of the Prevalence and Progression of Chronic Kidney Disease in a Rural Diabetic Cambodian Population

Abstract: BackgroundTo date, there are no known estimates of the prevalence of chronic kidney disease within Cambodia, the vast majority of whose citizens live in rural areas with limited access to renal replacement therapy.MethodsObservational analysis of patients from the Takeo province in Cambodia who presented to MoPoTsyo, a non-governmental organization, for screening and management of diabetes mellitus between 2010 and 2012 (n = 402; 75% females). Estimated glomerular filtration rate (eGFR) was calculated using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…38 Results from this organization indicate very favorable control of diabetes mellitus, hypertension, and CKD progression. 39 Similar results have been published for chronic disease outreach programs in the Philippines and the Democratic Republic of Congo. 40 Such screening and management interventions illustrate the importance and feasibility of chronic disease detection and management to delay progression, even in remote settings.…”
Section: Discussionsupporting
confidence: 75%
“…38 Results from this organization indicate very favorable control of diabetes mellitus, hypertension, and CKD progression. 39 Similar results have been published for chronic disease outreach programs in the Philippines and the Democratic Republic of Congo. 40 Such screening and management interventions illustrate the importance and feasibility of chronic disease detection and management to delay progression, even in remote settings.…”
Section: Discussionsupporting
confidence: 75%
“…Diabetes is costly to patients and their families. Diabetes-related complications, such as renal failure, are typically already highly prevalent at the time of diagnosis: a retrospective analysis from 483 people screened showed that among those diagnosed with diabetes mellitus, 57.5 % had an estimated glomerular filtration rate below 60 ml/min/1.73 m2 [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…1,3,[24][25][26][27][28][29][30][31] Because diabetes and hypertension are leading causes of ESRD, we determined the contribution of the global rise in these diseases to the rise in prevalence and incidence of maintenance dialysis (Figures 4 and 5). Results among countries providing partial versus universal dialysis were remarkably similar.…”
Section: Factors For Change: Population Burden Of Diabetes Mellitus Amentioning
confidence: 99%
“…Recent advances in treating and preventing communicable diseases coupled with the dramatic rise in the prevalence of diabetes and hypertension have initiated a shift in focus to the relationship between NCDs and morbidity, most recently in developing regions of the world. [1][2][3][4] This is exemplified by the United Nations 2012 Summit 2025 Initiative, which focuses on decreasing the burden of premature mortality to NCDs by 25% by year 2025.…”
mentioning
confidence: 99%